Physical, Textural, Rheological, and Sensory Characteristics of Amaranth-Based Wheat Flour Bread - Sahreen Nasir; Farhana Mehraj Allai; Murtaza Gani; Shaiq Ganaie; Khalid Gul; Aabida Jabeen; Darakshan Majeed (International Journal of Food Science)
In this study, the chemical composition, colour analysis, and antioxidant properties of flour and bread were analysed. We also examined the rheological properties of dough and proximate, colour, textural, and organoleptic properties of amaranth wheat bread. Wheat flour was replaced by amaranth flour (AF) at 0-15% levels (100 : 0, 95 : 5, 90 : 10, and 85 : 15, respectively). AF supplementation increased the moisture (31.06 to 33.24%), ash (0.92 to 1.51%), protein (12.17 to 13.11%), fat (2.16 to 2.77%), and crude fibre content (1.11 to 1.72%) of the bread while the nitrogen-free extract and alkali water retention capacity decreased from 52.58 to 47.65% and 136.00 to 112.02%, respectively. The antioxidant activity evaluated by DPPH, FRAP, and total phenolic content was reduced with increased levels of AF. A significant impact on the physical properties like the weight of bread (increased from 474.00 to 489.30 g), height (went down from 80.00 to 74.33 cm), loaf volume (decreased from 1580.00 to 1518.30 cm3), and specific volume (reduced from 3.32 to 3.10 cm3 g-1) was observed with the replacement of wheat flour. Textural measurement depicted that hardness, chewiness, gumminess, springiness, and cohesiveness increased with the substitution of amaranth flour. Rheological parameters like complex viscosity, loss modulus, and storage modulus were also observed in all dough samples. Bread samples with 5%, 10%, and 15% of AF showed lower yellowness (b∗) and higher lightness (L∗) and redness (a∗) values for crust colour while lower L∗ and higher a∗ and b∗ values for crumb colour. The bread prepared by replacing 5% and 10% of AF is nutritionally as well as sensorially acceptable.